Deciphering the Epidemiological Characteristics and Molecular Features of blaKPC–2- or blaNDM–1-Positive Klebsiella pneumoniae Isolates in a Newly Established Hospital - Chen, Ruifei; Liu, Ziyi; Xu, Poshi; Qi, Xinkun; Qin, Shangshang; Wang, Zhiqiang; Li, Ruichao (Frontiers in Microbiology, 2021)
The emergence of hypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) was regarded as an emerging puzzle in clinical settings. Here, we investigated the prevalence of CRKP strains among inpatients in a new hospital over one year since its inception with various techniques, and carried out a WGS-based phylogenetic study to dissect genomic background of these isolates. The genomes of three representative blaNDM-1 positive strains and the plasmids of four blaKPC-2 positive strains were selected for Nanopore long-read sequencing to resolve the complicated MDR structures. Thirty-six CRKP strains were identified from 193 K. pneumoniae isolates. These CRKP strains were grouped into five clusters and could be categorized into six major multilocus sequence types (MLSTs), including ST11, ST15, ST2237, ST37, ST1383 and ST304. Most of thirty blaKPC-2 positive strains (24/30) were assigned to ST11. The remaining six infant origin strains were positive for blaNDM-1. The blaNDM-1 gene was located on IncX3, IncFIB/IncHI1B and IncHI5-like plasmids, of which IncFIB/IncHI1B plasmid has a novel structure. Moreover, in silico virulome analysis identified several important virulence determinants (e.g., yersiniabactin, aerobactin, salmochelin, regulator of mucoid phenotype rmpA and transcriptional activator rmpA2) distributed in blaKPC-2 positive strains. Consistent with the Galleria mellonella larvae infection assay, siderophore secretion revealed the hypervirulence potential of most blaKPC-2 positive strains. Collectively, the widespread of hypervirulent blaKPC-2 positive K. pneumoniae in the newly established hospital was dominated by the clonal spread of ST11 K. pneumoniae, while blaNDM-1 positive K. pneumoniae isolates were concentrated in children cardiac ICU with polyclonal spread. Targeted measures should be implemented to prevent the grave consequences caused by hv-CRKP strains in nosocomial settings.